OPEN EDUCATION AND THE ROLE OF UNIVERSITY LIBRARIES IN THE MODERN INFORMATION SOCIETY - Grishchenko, Tamara B.; Zhydkova, Oksana O.; Еtenko Nataliia Y. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Highlights the trend of modernization of higher education in particular, and especially the principles of "open education", analyzes the major transformation taking place with libraries under the influence of this process, and their functional tasks in the new environment.